Buschke-Löwenstein tumor in a girl. A case report - Urbina Álvarez, Claudia (2021)
Buschke-Löwenstein tumor is a benign giant condyloma acuminatum, whose clinical lesions are larger than 10 cm, so the treatment of choice should always be surgical. We present the case of a one-year-old girl with giant condyloma of the vulva, a rapidly evolving Buschke-Löwenstein tumor, who underwent successful surgical resection. The literature was reviewed regarding its diagnosis and treatment.